Essentials of genetics - Klug, William S.; Cummings, Michael R.; Spencer, Charlotte A.; Palladino, Michael Angelo; Killian, Darrell (Pearson, 2021)
Known for its focus on conceptual understanding, problem solving, and practical applications, the bestselling Essentials of Genetics strengthens problem-solving skills and explores the essential genetics topics that today’s students need to understand. The 10th Edition has been extensively updated to provide comprehensive coverage of important, emerging topics such as CRISPR-Cas, epigenetics, and genetic testing. Additionally, a new Special Topics chapter covers Advances in Neurogenetics with a focus on Huntington Disease, and new essays on Genetics, Ethics, and Society emphasise ethical considerations that genetics is bringing into everyday life.--Provided by publisher.